Desain dan Pembuatan Inkubator berdasarkan Distribusi Temperatur - Budiono . (Jurnal Gamma, 2012)
Desain dan Pembuatan Inkubator berdasarkan Distribusi TemperaturBudionoStaf Pengajar Jurusan Teknik Mesin, Fakultas TeknikUniversitas Muhammadiyah Malang Email : budiono_ssi_mt_umm@yahoo.comABSTRACTWhen a new born babies (especially premature babies) have not been able to adjust to the temperature outside. One of the standard post-neonatal procedures are all newborns should be incorporated into the incubator, the time it takes depends on the level of health, durability and infant organ system itself. In this case the infant incubator is one tool that can help the newborn to adapt with the outside world, because the conditions in the womb to the outside world is very different, especially at a temperature problem. So with regular heating system so the baby can adapt to the transition period.Therefore, newborns should be helped to adjust to the new environment by putting them into the incubator. Infant incubator temperature is slowly lowered so that it can make the baby feel comfortable. In order for your baby comfortable at room temperature, then the distribution must evenly in incubator. To determine the pattern of temperature distribution in the incubator at my research will provide solutions to design and create an incubator temperature distribution based on the simulation results based on numerical approach with Matlab programKeywords: incubator, distribution, matlab